HUBUNGAN TINGKAT STRES DENGAN IDE BUNUH DIRI PADA MAHASISWA [THE RELATIONSHIP BETWEEN STRESS LEVELS AND SUICIDE IDEATION IN COLLEGE STUDENTS] - Grace Angel Lalenoh; Ian Berkat P.N Zega; Inggrid Febe Yuni; Maria V Ayu Florensa; Mega Tri Anggraini Setia Ningsih (Universitas Pelita Harapan, 2021)
The range of students ages are 18 – 24 years have a responsibility as students at college susceptible to stress even if exaggeration can trigger suicidal ideation.Suicide data for students aged 18-26 in America in 2016 reached 1,000 people/year, while in Indonesia the national death rate from suicide during the year of 2016 recorded 1,800 cases. Preliminary study results on 30 students: 45% think unable to continue life, 20% thought hopeless, 5% Think to harm themselves and 30% Have positive think to against stress. Objective: To determine the relationship of stress levels with suicide ideas in students. Research method used correlational quantitative research methods and purposive sampling techniques with a sample count of 250 respondents. Research instruments uses perceived stress scale valid (0.84) and reliable (Cronbach α 0.85) and Adult Suicidal Ideation Questionnaire (>1.96) reliable (Cronbach α 0.97). Results found the highest stress levels in the moderate stress category (80.0%) and the majority of suicidal ide ideas have a minimum risk (77.2), and there is a link between stress and suicidal dealing with a p-value of 0.048. Further research related to the application of adaptive stress coping and the provision of social support to students.BAHASA INDONESIA Mahasiswa yang termasuk dalam rentang usia 18-24 tahun memiliki tanggung jawab sebagai pelajar di Perguruan Tinggi rentan mengalami stres berlebihan sehingga dapat memicu ide bunuh diri. Data bunuh diri pada mahasiswa usia 18-26 di Amerika pada tahun 2016 mencapai 1.000 jiwa/tahun sedangkan data di Indonesia, angka kematian nasional akibat bunuh diri selama satu tahun terakhir pada tahun 2016 tercatat sebanyak 1.800 kasus. Studi pendahuluan pada 30 mahasiswa didapatkan sebanyak 45% berpikir tidak sanggup melanjutkan hidup, 20% berpikir putus asa, 5% berpikir menyakiti diri dan 30% berpikir positif terhadap stres. Tujuan penelitian untuk mengetahui hubungan tingkat stres dengan ide bunuh diri pada mahasiswa. Menggunakan metode kuantitatif korelasional dan menggunakan teknik purposive sampling dengan jumlah sampel 250 responden. Instrumen penelitian yakni Perceived Stress Scale yang valid (0,84) dan reliabel (Cronbach α 0,85) dan Adult Suicidal Ideation Questionnaire yang valid (>1,96) reliabel (Cronbach α 0,97). Hasil penelitian didapatkan tingkat stres terbanyak pada kategori stres sedang (80,0%) dan tingkat ide bunuh diri dengan mayoritas memiliki risiko minimal (77,2), serta terdapat hubungan antara stres dengan ide bunuh diri dengan hasil p value 0,048. Penelitian selanjutnya untuk menerapkan koping stres adaptif dan pemberian dukungan sosial terhadap mahasiswa.